``Mopheads'' as the target of verbal aggression in Czech media of 1960s and 1970s - Blaha, Ondrej (Bohemica Olomucensia, 2019)
The article examines reflecting on men's long haircuts in Czech media of 1960s and 1970s. The analysis of newspaper texts and selected TV programmes gives a clear impression of nonverbal and verbal strategies of manipulation and involvement of expressivity (which might be either self-evident, or disguised), and draws some general conclusions on the principles of public communication in totalitarian regime (which always could profit from social conformity and limited public awareness). The media texts, presenting the official standpoint of the Party and government, indicate that authorities were not willing to admit that some sociocultural matters were outside their control. Their criticism was, therefore, formulated in authoritarian, categorical and confident statements anchored in the ``scientific'' grounds of Communism: men with long hair were said to offend against ``taste and decency'', or even ``the hygienic practice''. All negative events in forward-looking and harmonious Czechoslovakia were presented as the influence of the western capitalist countries that threatened socialism directly, or at least supported the local enemies of the progress.
Keywords: Czech language; media; totalitarian regimes; 1960s; 1970s; Czechoslovakia; men's long haircuts; social conformity; language manipulation; expressivity; aggression